Implementation of the Non-Refoulment Principle in Indonesia: A Case Study of Rohingya Refugee Protection in Aceh - Taib, Mukhlis; Ali Buto, Zulfikar; Fithra, Herman; Alwi, Said; Iqbal, Muhammad; Safitri, Maya (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2024)
This study examines the implementation of the non-refoulement principle in Indonesia, focusing on the protection of Rohingya refugees in Aceh. The issue at hand involves the complex challenges faced due to the partial rejection of Rohingya refugees by some residents of Aceh, highlighting potential violations of international human rights norms. Despite Indonesia not ratifying the 1951 Refugee Convention, the country is bound by international human rights obligations, including the non-refoulement principle, which prohibits the forcible return of refugees to places where they face serious threats to their lives or freedoms. The primary objective of this research is to critically analyze how Indonesia, specifically Aceh, applies this principle and to explore the associated challenges and implications. The study employs a qualitative method, including a thorough review of international legal documents, such as the Universal Declaration of Human Rights (UDHR), the 1951 Refugee Convention, and the 1967 Protocol, alongside relevant literature. Findings reveal that while Indonesia shows commitment to non-refoulement, its implementation is inconsistent and hampered by resource constraints, lack of inter-agency coordination, and local resistance. This study's novelty lies in its detailed analysis of local responses, particularly in Aceh, an area often overlooked in previous research. The implications of this study stress the necessity for improved national policies and better coordination between governmental and non-governmental actors to ensure comprehensive protection for refugees. It also highlights that adherence to humanitarian principles can be achieved through practical actions, even in the absence of formal ratification of international conventions.